2021
DOI: 10.7554/elife.64412
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging and biophysical modeling support a button-based mechanism of somatic homolog pairing in Drosophila

Abstract: 3D eukaryotic genome organization provides the structural basis for gene regulation. In Drosophila melanogaster, genome folding is characterized by somatic homolog pairing, where homologous chromosomes are intimately paired from end to end; however, how homologs identify one another and pair has remained mysterious. Recently, this process has been proposed to be driven by specifically interacting 'buttons' encoded along chromosomes. Here, we turned this hypothesis into a quantitative biophysical model to demon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 80 publications
(130 reference statements)
2
19
0
Order By: Relevance
“…FISH analyses with embryos have indicated that the pairing of homologous chromosomes is largely abolished during progression through mitosis, followed by rapid restoration within the first 20 minutes of interphase [ 16 ]. Overall the most recent studies [ 17 19 ] support a model for homolog pairing based on “buttons”, i.e. high affinity regions interspersed along the chromosomes where pairing is initiated followed perhaps by zipper-like spreading.…”
Section: Introductionmentioning
confidence: 99%
“…FISH analyses with embryos have indicated that the pairing of homologous chromosomes is largely abolished during progression through mitosis, followed by rapid restoration within the first 20 minutes of interphase [ 16 ]. Overall the most recent studies [ 17 19 ] support a model for homolog pairing based on “buttons”, i.e. high affinity regions interspersed along the chromosomes where pairing is initiated followed perhaps by zipper-like spreading.…”
Section: Introductionmentioning
confidence: 99%
“…Mod(mdg4)_T (also designated as 67.2 or 2.2), the most extensively characterized isoform expressed from the complex mod(mdg4) locus, interacts and co-operates with several chromatin architectural proteins (including CP190, HIPP1 and SuHw) at the gypsy insulator [ 37 ]. Moreover, Mod(mdg4)_T in combinations with chromatin architectural proteins in various combinations is generally enriched at boundaries between topologically associated chromatin domains and also at button loci that promote the somatic pairing of homologous chromosomes [ 55 , 56 ]. Recently, Mod(mdg4) function has been implicated in a striking example of chromosome pairing-dependent regulation of physiological gene expression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous computational models have been described to represent meiotic homolog pairing [2][3][4][5][6][7]. These models have, in general, ignored the possibility of entanglement, by assuming that chromosomes are able to pass through one another.…”
Section: Plos Computational Biologymentioning
confidence: 99%